2014
DOI: 10.1002/chem.201404072
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Photoinitiating Systems for Holography Recording: Need for a Full Control of Primary Processes

Abstract: Optimization of holography recording in photopolymers was studied from the point of view of a quite general process, that is, the photogeneration of radicals. On the basis of a dye/coinitiator photoinitiating system, the effect of primary events and their relative efficiency was investigated with respect to the final overall properties, such as the diffraction efficiency. Quenching of the dye excited states by the borate salts coinitiators exhibits important differences depending on the dye used (Rose Bengal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…The reaction mechanism of the photoinitiating system was studied through laser flash photolysis and fluorescence. After light absorption in acetonitrile, SFH + is known to yield a singlet state (singlet state energy E S =2.41 eV, lifetime τ S =3.9 ns) and a triplet state (triplet state energy E T =1.83 eV, quantum yield ϕ T =0.51). The photoinduced electron transfer (PET) from tetrabutylamonium tetraphenylborate (TPB) salt to SFH + excited states was found to be exergonic for both singlet and triplet states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mechanism of the photoinitiating system was studied through laser flash photolysis and fluorescence. After light absorption in acetonitrile, SFH + is known to yield a singlet state (singlet state energy E S =2.41 eV, lifetime τ S =3.9 ns) and a triplet state (triplet state energy E T =1.83 eV, quantum yield ϕ T =0.51). The photoinduced electron transfer (PET) from tetrabutylamonium tetraphenylborate (TPB) salt to SFH + excited states was found to be exergonic for both singlet and triplet states.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, safranine O (SFH + ) combined with tetraphenylborate salt as electron donor and a triazine derivative as electron acceptor was selected as photoinitiating system (PIS). Safranine has been shown to behave very efficiently in three component PIS for holographic recording and other photopolymerization processes . Molecular formulas of used compounds are displayed in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] The quenching rate constants were measured by LFP for triplet states and fluorimetry for singlet states (see Table 1) and are found to be in good agreement with ΔG et values. The quenching rate constant of 3 …”
Section: Molecular Photochemistrymentioning
confidence: 99%
“…A sinusoidal modulation of the refractive index is thus obtained in the photopolymerizable matrix. [1,2] It was demonstrated that the efficiency of light conversion into chemical energy directly impacts the refractive index modulation [3] and the final properties of the holographic grating. The aim of this paper is to study the effect of three-component photoinitiating system (PIS based on a dye, a coinitiator and a redox additive) on the efficiency of holographic grating recording.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported the radical generation ability of safranin in combination with different coinitiators. [42][43][44][45] Therefore, in this study, a threecomponent PIS based on safranin O was employed in digital light processing 3D printing to investigate the dual function of the dye as photosensitizer and photoabsorber. As mentioned before, the former was responsible for active species production and the latter could play a role in controlling the curing depth and improving the vertical resolution of printed parts.…”
Section: Introductionmentioning
confidence: 99%